Respons Beberapa Tanaman Sayuran Bermikoriza terhadap Dosis P pada Sistem Hidroponik Model Ebb Flow - Derisfha Anggraeni; Anne Nurbaity; Emma Trinurani Sofyan (Fakultas Pertanian Universitas Padjadjaran, 2019)
Hydroponics is one of the urban farming techniques that can be used to improve crop yield. Nowadays, the supply of all nutriens in hydroponics, particulary phosphate only derived from inorganic fertilizers. Application of arbuscular mycorhiza fungi (AMF) as bioagent may help plants to fill its nutrient need, especially phosphate. This study aimed to find out the best concentration of phosphate fertilizer to be applied to the hydroponic Ebb-flow system model. The stage was to test several vegetable plants with various concentrations of phosphorus (0, 20, 40, 80 ppm) on the Ebb-flow hydroponic system. Vegetables used were romaine lettuce, red lettuce, and kale. Interaction was found between vegetables and the variety of phosphate concentrations and the root colonization by AMF, and phosphate uptake. The AMF applications on the hydroponic Ebb-Flow system model reduced phosphate fertilizer need by 40 ppm (50%), on red lettuce 0 ppm (100%), and on kale 20 ppm (25%). Besides lowered phosphate doses, such applications also increased the plant yield.